NALAR SUFISTIK PADA KISAH AL-QUR’AN - BASRI; Misbahuddin Asaad; Isnayanti (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2025)
This study aims to describe the Sufi nuances of al-Naisaburi's interpretation model of the story of the Qur'an in the book of interpretation Ghara'ib al-Qur'an wa Ragha'ib al-Furqan. The Sufi approach in interpreting the Qur'an has raised pros and cons, but this is not a signal to be a priori with this kind of interpretation model. So far, the presentation of the story of the Qur'an has been dominated by a textual interpretation model. In fact, by revealing the story of the Qur'an from the inner side, it will provide new colors and nuances in understanding the wisdom behind the narrative of the story in the Qur'an. By using a descriptive-analytical method, this study describes and analyzes the results of al-Naisaburi's interpretation related to the story of the prophet Moses. The results of this study indicate that the portrait of al-Naibari's interpretation of QS. al-Baqarah: 67-68 shows his skill in combining the literal and inner meanings of a verse. Reading the story in the Qur'an feels less effective in life if it is only to know the chronological flow of an event that occurred in the past by only paying attention to its textual meaning. However, if the verses of the story in the Qur'an are explored with Sufi reason, then the inner meaning contained in it will be seen which is full of wisdom and deep knowledge of the events that occurred in the story.